For all positive integers n ,
1 + 2 + 3 + ⋯ + n = 2 n ( n + 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are both correct in our approaches to the problem. The difference is that you have provided the derivation for the formula (how the formula was created in the first place) while I have provided the verification of the formula (will this work for all positive integer n ).
First, let us see if this is true for n = 1
2 1 ( 1 + 1 ) = 2 1 ( 2 ) = 2 2 = 1 , 1 = 1 so it is true for n = 1
Let's assume it is true for n = r , so that 1 + 2 + 3 + ⋯ + r = 2 r ( r + 1 )
Now let us see if it is true for n = r + 1
1 + 2 + 3 + ⋯ + r + ( r + 1 ) = 2 r ( r + 1 ) + ( r + 1 )
That equals 2 r ( r + 1 ) + 2 ( r + 1 ) = 2 ( r + 1 ) ( r + 2 ) = 2 ( r + 1 ) ( ( r + 1 ) + 1 )
If the statement is true for r and r + 1 , it must be true for all positive integers. Q.E.D.
I have a "proof" (not really sure if it is flawless or not) based off of magic squares.
We can derive the magic constant like so: s = x ∑ i = 1 x 2 , where s is the magic constant.
We can also find the constant like so: s = x ⋅ m , where x is the order of the square and m is the median.
We get the final equation: ∴ ∑ i = 1 x 2 x = x 2 m .
So the sum from 1-n is n*the median. Thought you might like to see how I found this accidentally from solving puzzles.
1 + 2 + 3 + ... + n = n(n+1)/2
Proof:
Now, add this equation to it self.
1 + 2 + 3 + ... + n
+n + n-1 + n-2 +... 1
= n+1 +n +1 + n+1....(n times)
2(1+ 2 + 3+ ...+ n) = n(n+1)
Thus: 1 + 2 +3 +.. + n = (n(n+1))/2
Problem Loading...
Note Loading...
Set Loading...
A much simple proof for this question is, let the sum of them be ζ , then we will get ζ = 1 + 2 + 3 + ⋯ + n
Now reverse it, then we get ζ = n + ( n − 1 ) + ( n − 2 ) + ⋯ + 3 + 2 + 1
Combining them, we will get 2 ζ = n t e r m s ( n + 1 ) + ( n + 1 ) + ⋯ + ( n + 1 ) = n ( n + 1 )
Hence ζ = m = 1 ∑ n m = 2 n ( n + 1 )